Selecting reasonable soil moisture-maintaining measures to improve the soil physicochemical properties and achieve high yield and quality of purple garlic in the China Hexi Corridor oasis agricultural area - Pan, Xiaofan; Zhang, Hengjia; Deng, Haoliang; Yu, Shouchao; Zhou, Chenli; Li, Fuqiang (Frontiers in Plant Science, 2024)
Agricultural plastic film, as an important agricultural production material in the China Hexi Corridor oasis agricultural area, is widely used in the intensive production process of purple garlic. Specifically, in the Minle area of the Hexi Corridor, we selected ordinary transparent plastic film, transparent oxo-biodegradable plastic film, ordinary black plastic film, black oxo-biodegradable plastic film, wheat straw, and aubergine-super absorbent polymers, and used the traditional open field as a control. To analyze the effects of different moisture maintaining measures on farmland soil quality, garlic yield and quality, and water-fertilizer productivity in purple garlic. The results showed that all the moisture maintaining measures could increase garlic yield, improve bulb quality and water-fertilizer productivity, and improve the soil hydrothermal conditions, maintain soil fertility, increase the microbial quantity, improve enzyme activity, Overall, transparent plastic film mulching was superior to black plastic film mulching, straw mulching and A-SAP, with 110 d transparent oxo-biodegradable plastic film mulching being the most effective. Compared with other moisture maintaining measures, the yield, water productivity, irrigation water productivity and nitrogen fertilizer partial factor productivity of purple garlic were significantly increased by 13.33% to 119.77%, 13.81% to 126.77%, 13.41% to 119.95% and 13.33% to 119.76%. Meanwhile, the contents of allicin, soluble sugar, soluble protein, crude fibre and amino acid content were increased by 1.44% to 14.66%, 4.64% to 36.46%, 0.38% to 28.27%, 1.89% to 26.29% and 0.38% to 3.74%. Based on the TOPSIS method, the soil quality was evaluated, and the yield, quality and water productivity of garlic were comprehensively evaluated under each moisture maintaining measure using principal component analysis. it was determined that the best soil quality and better bulb quality as well as higher garlic yield and water productivity were obtained when using the 110 d induction period transparent oxo-biodegradable plastic film. It can be used as a more reasonable moisture maintaining measure and technical reference for the purple garlic industry in the China Hexi Corridor oasis agricultural area, which can ensure the improvement of quality and stabilization of yield and also solve the risk of environmental pollution caused by plastic film mulching at the source.